Plan de gestión de monitoreo y asesoramiento para mejorar el desempeño Docente en la Institución Educativa Nº 18345 La Morada, Amazonas - 2016 - Ynga Rojas, Emma de Jesús (2019)
ABSTRACT In the study of this research it was proposed as a general objective of: demonstrate that the monitoring and advisory management plan improves the teaching performance in the Educational Institution N ° 18345 La Morada, Amazonas - 2016, considering as hypothesis; the monitoring and advisory management plan improves the teaching performance in Educational Institution N ° 18345 La Morada, Amazonas - 2016. The experimental type of study, with pre-experimental design, the methods used were the inductive, deductive, analytical and of synthesis. The population and sample were made up of 24 teachers, a questionnaire of 17 items was used according to the dimensions Preparation for student learning, (9 items) Teaching for student learning, (8 items). The results were presented in tables and statistical figures. To check whether the monitoring and advisory management plan improves teaching performance, we used the T Student, whose statistical value was 16,295, higher than the theoretical value of 1,714 with a significance level of, 000 less than 0.05, observing that the teaching performance improved significantly when the monitoring and advisory management plan became operational, so this research is important, proving that from a high level of 0% in the pre-test, it was improved by 88% high level with the post test